2017
DOI: 10.1016/j.it.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

PSGL-1: A New Player in the Immune Checkpoint Landscape

Abstract: P-selectin glycoprotein ligand-1 (PSGL-1) has long been studied as an adhesion molecule involved in immune cell trafficking and is recognized as a regulator of many facets of immune responses by myeloid cells. PSGL-1 also regulates T cell migration during homeostasis and inflammatory settings. However, recent findings indicate that PSGL-1 can also negatively regulate T cell function. As T cell differentiation is finely tuned by multiple positive and negative regulatory signals that appropriately scale the magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 111 publications
2
79
0
4
Order By: Relevance
“…Recently, it has been highlighted the role of PSGL-1 as an immune checkpoint regulator that promotes T-cell exhaustion [55]. Specifically, in cancer environment it has been found that PSGL-1-deficiency enhanced T-cell antitumor immunity to melanoma [56]. In line with these data, for the first time, we reported a putative correlation between the expression of PD-L1 by prostate cancer cells and the presence of PSGL-1 positive intratumoral inflammatory infiltrate.…”
Section: Discussionsupporting
confidence: 81%
“…Recently, it has been highlighted the role of PSGL-1 as an immune checkpoint regulator that promotes T-cell exhaustion [55]. Specifically, in cancer environment it has been found that PSGL-1-deficiency enhanced T-cell antitumor immunity to melanoma [56]. In line with these data, for the first time, we reported a putative correlation between the expression of PD-L1 by prostate cancer cells and the presence of PSGL-1 positive intratumoral inflammatory infiltrate.…”
Section: Discussionsupporting
confidence: 81%
“…However, there are multiple reasons for enthusiasm about this discovery. First, the roles of PSGL‐1 and VISTA in regulating T cell activities and tumor immunity is gaining traction . Secondly, the pH and ionic environment being a factor that regulates immune receptor interactions is a novel and valuable concept.…”
Section: The Vista Ligand Mysterymentioning
confidence: 99%
“…[13] PSGL-1 is both a key ligand for rolling adhesion and a receptor to enable intracellular signaling, inducing cytokine secretion, activation of SRC family kinase, ÎČ2-integrin, and potential activation of Phosphoinositide 3kinase (PI3K) signaling in either neutrophils or the endothelial cells they are rolling on. [14] In this paper, rolling adhesion is used as an assay to directly probe how PSGL-1 expression is affected by T2D conditions using controlled substrate P-selectin concentration. Our aim is to investigate how neutrophil rolling is affected by T2D-like pro-in ammatory conditions, such as hyperglycemia, and supraphysiological TNF-α, IL-6, and insulin concentrations, related solely to the interaction between PSGL-1 and P-selectin.…”
Section: Introductionmentioning
confidence: 99%